Preclinical Evaluation of 68Ga-labeled RGD Peptide for Detection of Malignant Angiogenesis - O. E. Klementyeva; A. B. Bruskin; A. S. Lunev; M. G. Rakhimov; K. A. Luneva; G E. Codina (Разработка и регистрация лекарственных средств, 2020)
Introduction. The early detection of tumor growth remains one of the most important tasks of diagnostic nuclear medicine. The vascular growth being created malignant neoplasms is a good target for the purpose. The molecular participants in the process are gallium-68 labeled vector to the delivery of radionuclides and positron-emission tomography (PET) imaging.Aim. Possibility researching of using the complex gallium-68 labeled peptide sequence RGD for PET imaging of tumor with different grade of neovascularization.Materials and methods. Complex compound of Ga-68 with the peptide NODAGA-cRGD2 (the proposed name used below is «Vascular, 68Ga») was used for studying of the distribution in mice with transplanted heterotopic xenografts of glioblastoma U-87 MG and breast adenocarcinoma Ca-755 after intravenous injection, as well as the possibility of visualization the tumor.Results and discussion. The «Vascular, 68Ga» biodistribution in the mice body is usual of laboratory animals is usual of the behavior of peptides in vivo: rapid clearance from the blood, intense urinary excretion. The accumulation of the drug in the area of glioblastoma in mice is on average 2 times higher than that in adenocarcinoma. The results of in vivo PET imaging of experimental tumor lesions correlate well with ex vivo radiometry data. Conclusion. The «Vascular, 68Ga» actively accumulated in well-vascularized tumor foci after intravenous injection and rapidly excreted from the body through the kidneys without noticeable non-specific accumulation in other organs and tissues. The PET imaging possibility of experimental tumor foci was shown.